PENGARUH CITRA MEREK, DESAIN PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU COMPASS PADA “MARKETPLACE TOKOPEDIA” - Rendi, Rendi; Ernestivita, Gesty (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to analyze the effect of brand image, product design, and price on the purchasing decision of Compass shoes. Brand image is the consumer's perception of a particular brand, while product design refers to the physical and aesthetic characteristics of Compass shoes. The price reflects the value that consumers have to pay to obtain Compass shoes. The research sample consists of consumers who have the potential to buy Compass shoes. The data obtained were analyzed using multiple regression analysis techniques to examine the relationship between the independent variables (brand image, product design, and price) and the dependent variable (purchasing decision). The results of the study show that brand image, product design, and price have a significant influence on the decision to purchase Compass shoes. A positive and strong brand image, attractive product design, as well as reasonable prices and in accordance with the perceived value of consumers, can increase the consumer's tendency to buy Compass shoes. This finding has important implications for the shoe company Compass in developing their marketing.